2019
DOI: 10.1002/jcp.28255
|View full text |Cite
|
Sign up to set email alerts
|

NLRC3 inhibits MCT‐induced pulmonary hypertension in rats via attenuating PI3K activation

Abstract: Phosphoinositide 3‐kinase (PI3K) activation plays a critical role in the pulmonary vascular remodeling of pulmonary hypertension (PH). The nucleotide‐oligomerization domain (NOD)‐like receptor subfamily C3 (NLRC3) inhibits proliferation and inflammation via PI3K signaling in cancer. We previously showed NLRC3 was significantly reduced in PH patients, but the mechanism of function remains unclear. This study aimed to determine the potential role of NLRC3 in PH. We found that NLRC3 was downregulated in the pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Saline was given to the control group as placebo. For the other four groups, MCT (60 mg/kg) [24,25] was injected into the subcutaneous tissue to induce progressive pulmonary arterial hypertension at the end of 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…Saline was given to the control group as placebo. For the other four groups, MCT (60 mg/kg) [24,25] was injected into the subcutaneous tissue to induce progressive pulmonary arterial hypertension at the end of 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…14 Zha et al revealed that NLRC3 protected against monocrotaline (MCT)-induced rat pulmonary hypertension (PH) and platelet-derived growth factor-BB (PDGF-BB)induced PASMCs proliferation, migration, and inflammation through a mechanism involving PI3K inhibition. 15 Of note, recent studies have focused on the function of NLRC3 in carcinogenesis and tumor development. 9,10 However, the expression of NLRC3 in bladder cancer tissues and its potential clinical and biological significances have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…NLRC3/PI3K pathway is a newly discovered intriguing signaling pathway that has been reported to mediate cell survival in multiple cancer types. 32,33 Initial studies have shown that NLRC3 is primarily involved in innate immune responses. Moreover, it has been confirmed to alleviate nonspecific immune responses during virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray data and bioinformatics analysis showed that NLRC3 and AKT signaling pathway might be key downstream mediators. NLRC3/PI3K pathway is a newly discovered intriguing signaling pathway that has been reported to mediate cell survival in multiple cancer types 32,33 . Initial studies have shown that NLRC3 is primarily involved in innate immune responses.…”
Section: Discussionmentioning
confidence: 99%